“Cerita Corona” Application As Learning Media - Dase Erwin Juansah; Ade Husnul Mawadah; Ade Anggraini Kartika Devi (AL-ISHLAH: Jurnal Pendidikan, 2022)
Online learning during the Covid-19 pandemic triggered the acceleration of the digitization of learning media. Media digitization could be done in the form of mobile learning applications that were in accordance with today's lifestyle. Learning media in the form of applications on mobile phone were expected to provide a meaningful learning experience so that students were not bored and the learning objectives were achieved maximally. However, in reality, not all teachers were ready and able to independently create digital learning media. This study aimed to develop a children's storybook application with the theme of Covid-19 to help children and teachers obtained learning media whose content was in accordance with current issues. This study used the Educational Design Research (EDR) model. The educational design research (EDR) model has stages 1) analysis and exploration; 2) design and construction; and 3) evaluation and reflection. From the results of expert validation, practitioners, and trials, a children's story book with the Covid-19 theme, named "Cerita corona" was successfully developed and met the eligibility criteria.